Psidium guedesiae a new species from the Caatinga of Northeastern Brazil - Stadnik, Aline; Landrum, Leslie R. (Phytotaxa, 2025)
Psidium is one of the largest genera of Myrtaceae in Brazil. Bahia, the most species rich state, has species growing in the Cerrado, Caatinga, and Atlantic Forest domains, and the ecotones between these. A new species, Psidium guedesiae, is described from the Caatinga of Northeastern Brazil. It is compared to three similar species of Psidium that all seem to grow in the Caatinga habitat. A key to the species of this group is provided. The morphology, phenology, ecology and conservation status of P. guedesiae are discussed.